2015
DOI: 10.1248/bpb.b14-00525
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Discrimination of Plasmalemmal and Mitochondrial Sodium–Calcium Exchanger in Cardiomyocyte-Derived H9c2 Cells

Abstract: The Na + -Ca 2+ exchanger (NCX) is involved in the physiological and pathophysiological regulation of intracellular Ca 2+ concentration in various cell types including cardiomyocytes. Although the major role of plasmalemmal NCX in cardiomyocytes is to extrude Ca 2+ from the cell and maintain low cytoplasmic Ca 2+ concentration, 1) NCX is also considered to be responsible for the pathogenesis of ischemia-reperfusion and arrhythmia.2,3) Concerning pharmacological inhibition of NCX, SEA0400 {2-[4-[(2,5-difluoroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Extrusion of mitochondrial Ca 2+ is mediated primarily via mitochondrial Na + -Ca 2+ exchanger, which is activated by Na + gradients between the matrix and the cytosol [19] and is inhibited by diltiazem [21] . We have shown in our pervious study that inhibition of the mitochondrial uniporter inhibited, while mitochondrial Na + -Ca 2+ exchanger inhibition enhanced, the rise in mitochondrial Ca 2+ concentration on elevation of extramitochondrial Ca 2+ concentration [14] . In the present study, the extramitochondrial Ca 2+ -induced decrease in mitochondrial calcein fluorescence was inhibited by ruthenium red and enhanced by diltiazem (Fig.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Extrusion of mitochondrial Ca 2+ is mediated primarily via mitochondrial Na + -Ca 2+ exchanger, which is activated by Na + gradients between the matrix and the cytosol [19] and is inhibited by diltiazem [21] . We have shown in our pervious study that inhibition of the mitochondrial uniporter inhibited, while mitochondrial Na + -Ca 2+ exchanger inhibition enhanced, the rise in mitochondrial Ca 2+ concentration on elevation of extramitochondrial Ca 2+ concentration [14] . In the present study, the extramitochondrial Ca 2+ -induced decrease in mitochondrial calcein fluorescence was inhibited by ruthenium red and enhanced by diltiazem (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Two dimensional images of calcein fluorescence were obtained under excitation at 488 nm. Tetramethylrhodamine ethylester (TMRE) and Rhod 2 fluorescence was imaged under excitation at 514 nm by confocal and epifluorescence microscopy as in our previous studies [8,13,14] . The time course of the whole cell fluorescence intensity was calculated with Aquacosmos software (Hamamatsu Photonics).…”
Section: Methodsmentioning
confidence: 99%
“…3). SEA0400, at a concentration of 1 µM which shows marked inhibition of the plasmalemmal NCX in various cells including H9c2 cells, 18) had no effect on mitochondrial Ca 2+ both under normal and ischemic conditions. This indicates that SEA0400 inhibits neither the Ca 2+ uniporter nor the mitochondrial NCX, and has no direct effect on mitochondrial Ca 2+ transport pathways.…”
Section: Discussionmentioning
confidence: 91%
“…The experimental system was basically the same as that described in our previous reports . 7,8) Rat embryonic heart derived H9c2 cells were cultured in Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% FBS. To obtain mitochondrial-targeted yellow cameleon DNA, its full-length cDNA 11) was inserted into an expression vector which has a mitochondria targeting signal sequence, pEYFP-mito (Clontech, Palo Alto, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Using this system, we previously reported that SEA0400 affects neither mitochondrial Ca 2+ entry nor Ca 2+ extrusion. 7,8) Concerning the effect of KB-R7943 on mitochondrial Ca 2+ transporters, conflicting results have been reported depending on the cell type. 9,10) In the present study, we intended to clarify the effect of KB-R7943 on mitochondrial Ca 2+ transport in cardiomyocytes using the H9c2 cell system described above.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%